FLAME ATOMIC ABSORPTION SPECTROMETRIC DETERMINATION OF NICKEL AND CHROMIUM IN VARIOUS PLANT LEAVES USED AS BIOMONITORS IN ENVIRONMENTAL POLLUTION - Avci, Halim; Kaya, Gokce; Akdeniz, Ismail; Ince, Muharrem; Yaman, Mehmet (Parlar Scientific Publications (P S P), 2013)
Levels of nickel and chromium in leaves of 14 plant species grown in industrial sites of Gaziantep and surrounding were examined for biomonitoring of atmospheric pollution using flame atomic absorption spectrophotometry (FAAS). The plant leaf samples were collected from different locations with different degrees of metal pollution. The metal levels in the plants were in the ranges of (with mean values) 0.4-28.0 (3.1) mg kg(-1) for Ni and 0.1-6.6 (1.5) mg kg(-1) for Cr. On the other hand, the Ni and Cr levels in the plant leaf samples collected from control) areas were in the ranges of 0.4-2.1 (1.1) and 0.1-1.4 (0.58) mg kg(-1), respectively. It was concluded that Pinus nigra L., Acacia robinia L., Platanus orientalis L., Nerium oleander L., Pyracantha coccinea M.Roem. and Populus nigra L. for Ni, Pinus nigra L., Acacia robinia L., Olea europaea L. and Nerium oleander L. for Cr could be biomonitors. Therefore, it was demonstrated that the plant leaves could be used for heavy metal air pollution monitoring in urban and industrial regions.
Keywords: Biomonitoring; trace elements; environmental pollution; leaf; atomic absorption